Hantavirus pulmonary syndrome in Argentina, 1995-2008 - Martinez, Valeria Paula (2010)
We report a large case series of hantavirus pulmonary syndrome (HPS) in Argentina that was confi rmed by laboratory results from 1995 through 2008. The geographic and temporal distribution of cases by age, sex, fatality rate, and risk factors for HPS was analyzed. A total of 710 cases were unequally distributed among 4 of the 5 Argentine regions. Different case-fatality rates were observed for each affected region, with a maximum rate of 40.5%. The male-to-female ratio for HPS case-patients was 3.7:1.0; the case-fatality rate was signifi cantly higher for women. Agriculture-associated activities were most commonly reported as potential risk factors, especially among men of working age. Although HPS cases occurred predominantly in isolation, we identifi ed 15 clusters in which strong relationships were observed between members, which suggests ongoing but limited person-to-person transmission.